Transition metal-catalyzed pyridine synthesis - Wu, Xiao-Feng, 1985- (Amsterdam : Elsevier Science, 2016)
Transition Metal-Catalyzed Pyridine Synthesis provides an overview of pyridines, describing properties of these heterocycle compounds and describing traditional synthetic procedures for them. The book then explores catalyzed procedures for pyridine synthesis in greater detail and depth than is currently available in published Review articles. The short series Transition Metal-Catalyzed Heterocycles Synthesis, authored by Xiao-Feng Wu, summarizes recent achievements on heterocycles synthesis with transition metal as the catalysts, with each volume dedicated to one heterocycle compound.
Front Cover; Transition Metal-Catalyzed Pyridine Synthesis; Copyright Page; Dedication; Contents; 1 Introduction; Reference; 2 Synthesized by Intramolecular Cyclizations; References; 3 Synthesized by Intermolecular Cyclizations; 3.1 Synthesized by [2+2+2] Cyclization Reactions; 3.2 Synthesized by [2+2+1+1] Cyclization Reactions; 3.3 Synthesized by [3+3] Cyclization Reactions; 3.4 Synthesized by [3+2+1] Cyclization Reactions; 3.5 Synthesized by [4+2] Cyclization Reactions; 3.6 Synthesized by [5+1] Cyclization Reactions; References; 4 Summary and Outlook; Back Cover.
Online resource; title from PDF title page (EBSCO, viewed February 15, 2016).
Includes bibliographical references.
Keywords: Pyridine -- Synthesis; Transition metal complexes; SCIENCE -- Chemistry -- Organic; Pyridine -- Synthesis; Transition metal complexes; Electronic books; Electronic book